CONSTRUCTING SINGAPORE'S CULTURAL AND POLITICAL NARRATIVES: A STUDY ON LEE KUAN YEW'S CONTROL OF THE MEDIA TO BUILD SINGAPORE - Buni Yani (Celt: A Journal of Culture, English Language Teaching & Literature, 2008)
There are several ways how to understand culture - and also politics - in one country. One way is to look at the media that become the backbone of communication between the state and the people. The powerful media can be used to form people's understanding on "narratives" created by the state. The narratives on politics. freedom of the press. development. and economy are constructed in such a way that people cannot but accept what are presented through the media. Singapore'sfoundingfather Lee Kuan Yew - and also his successors - understood the powerful media could bring aboutfor Singapore's culture and politics. That is wiry Lee -and his successors - used the media to build andform Singapore's culture in the first place. Singapore's ethnic and cultural diversities - which consist of the Chinese. Indians. and Malays - are regarded as a potential conflict if the state fails to set up a "common denominator" for all Singaporeans. Based on this ground. Lee and his successors figured out what to do to cope with this problem. Lee and his successors came to a conclusion that Singapore government should make use of the media to spread the idea of Singapore culture of which characteristics are pluralistic. cosmopolitan. and meritocratic. The media have contributed to spread the so-called rujak lal/guage - or widely known as Singlish - a unique Singaporean English blended with Chinese. Malay and Indian. Singapore's broadcast media policy - radio and television - are deeply influenced by Lee Kuan Yew's vision of the city state. The media have been used to construct good narratives on Singapore's culture and politics.